Barbarians at the gate [videorecording (DVD)] - Jordan, Glenn, 1936-; Garner, James. 1928-2014; Pryce, Jonathan; Riegert, Peter, 1947-; Cassidy, Joanna, 1945-; Burrough, Bryan, 1961- (HBO Home Video, 2001)
In the 1980s, everyone was making the big bucks and F. Ross Johnson, CEO of RJR Nabisco, wants to make his fortune. He decides to buy out the Nabisco shareholders and take over his company in order to escape the tyranny of the stockholders. Johnson is introduced to the master of the leveraged buyout, Henry Kravis, but afraid of losing the company to this sharp dealer, he decides to make his move with Peter Cohen. Kravis mounts his own buy-out campaign, which leads to a battle for control of Nabisco.